2013
DOI: 10.1287/mksc.2013.0773
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic vs. Image-Related Utility in Social Media: Why Do People Contribute Content to Twitter?

Abstract: We empirically study the motivations of users to contribute content to social media in the context of the popular microblogging site Twitter. We focus on noncommercial users who do not benefit financially from their contributions. Previous literature suggests that there are two main types of utility that motivate these users to post content: intrinsic utility and image-related utility. We leverage the fact that these two types of utility give rise to different predictions as to whether users should increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
258
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(271 citation statements)
references
References 58 publications
2
258
0
3
Order By: Relevance
“…We review this work below and discuss the relationships between consumer similarities, goals, and online WOM; we then consider the implications of this framework for linguistic mimicry. 8 WOM, Goals, and Similarity Consumers derive utility from sharing WOM (Berger 2014), and do so for many reasons (e.g., Hennig-Thurau et al 2004;Toubia and Stephen 2013). Prior work has shown that online WOM can help consumers satisfy two important goals: affiliation and achievement (Relling, Schnittka, Sattler and Johnen 2016).…”
Section: Behavioral and Linguistic Mimicrymentioning
confidence: 99%
“…We review this work below and discuss the relationships between consumer similarities, goals, and online WOM; we then consider the implications of this framework for linguistic mimicry. 8 WOM, Goals, and Similarity Consumers derive utility from sharing WOM (Berger 2014), and do so for many reasons (e.g., Hennig-Thurau et al 2004;Toubia and Stephen 2013). Prior work has shown that online WOM can help consumers satisfy two important goals: affiliation and achievement (Relling, Schnittka, Sattler and Johnen 2016).…”
Section: Behavioral and Linguistic Mimicrymentioning
confidence: 99%
“…Monetary incentive has been identified by prior studies as one of the most important motivations to promote effort and performance, along with intrinsic motivation and image motivation (e.g., Benabou and Tirole 2003, Tang et al 2012, Toubia and Stephen 2013, to name a few). Although economic theories suggest that an increase in financial rewards provided by an activity can improve the effort and performance of participants, some studies (e.g., Deci et al 1999, Gneezy andRustichini 2000) show that contingent rewards can also be counterproductive, especially in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, females have been found to exhibit more sociallyorientated traits. It has been found that females tend to feel more empathy [49] and exhibit greater sensitivity to social cues [19] and others' moods and affect [50]. Because females are more socially attuned, they are more likely to notice others' unfavorable circumstances [51], and thus are more likely, in turn, to respond to others' needs.…”
Section: Social Value Orientation Theory and The Role Of Gendermentioning
confidence: 99%